Phylogeographic analyses detect population structure and limited gene flow in the Peacock Grouper Cephalopholis argus across Micronesia - Amirthalingam, Pavithiran; Greaves, Samuel; O’Malley, Joseph M.; Schemmel, Eva; Marciante, Victoria; Gaither, Michelle R. (Frontiers in Marine Science, 2025)
Coral reefs are patchily distributed across vast areas of Earth’s tropical and subtropical oceans. Dispersal of individuals between habitat patches is essential to maintain genetic connectivity between subpopulations and plays an important role in population persistence. While the biotic and abiotic factors that influence patterns of dispersal have received a great deal of attention, fundamental questions about genetic connectivity in marine systems remain largely unanswered. Micronesia, in the northern central Pacific, is comprised of over two thousand islands that stretch across 7,400,000 km2 and is thought to provide stepping-stones for dispersal between the central and western Pacific. Despite its size and importance, few phylogeographic studies have focused on Micronesia and none have been conducted in the Mariana Archipelago in northern Micronesia. Here we examined population structure in the peacock grouper Cephalopholis argus across the region. Based on 15,000 SNPs we found three population clusters: the Mariana Archipelago, western Micronesia (Palau) and eastern Micronesia (Pohnpei and Kwajalein). These findings are largely concordant with two previous studies and taken together they highlight the influence of the North Equatorial Current and the North Equatorial Countercurrent in the Central Pacific and indicate that perhaps broad scale ecosystem level processes and not species-level traits are driving population patterns in the region. Furthermore, we detected little genetic structure across 800 km of the Mariana Archipelago and found that rates of gene flow among the islands were higher in the north but diminished at Anatahan and continued to decrease southward toward Saipan and Guam. Our data also indicate that the Mariana Islands receives more migrants from the Central Micronesian islands to the south then it exports, and that Guam, the southernmost island in the archipelago, may serve as an important gateway from the Central Pacific into the Mariana Islands.